PCOS Disease Classification Using XGBoost Algorithm and Genetic Algorithm for Feature Selection - Atika, Enda Putri; Nadzirullah, Muh. Ilham; Arindika, Alti (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2025)
Polycystic Ovary Syndrome (PCOS) is an endocrine disorder that often occurs in women of reproductive age, with a global prevalence of 10-16%. The diagnosis of PCOS is still a challenge due to the uncertainty of the cause, which can worsen the patient's condition due to delayed detection. This study aims to develop a classification model to detect PCOS using a combination of SMOTE algorithm, genetic algorithm, and XGBoost. The dataset used is a public dataset from Kaggle entitled